Comparison of interrupted-X technique closure versus conventional continuous closure of rectus sheath: a randomized control study - C., Balaji; Neogi, Sushanto; Ramasamy, Sadasivam; Vats, Manu (International Surgery Journal, 2019)
Background: A major surgical complication after emergency midline laparotomy is abdominal fascial dehiscence. Dehiscence is associated with increased morbidity and mortality rates up to 30%, prolonged hospital stay, and a long-term risk of developing incisional hernia. The risk factors of Wound dehiscence can surgeon factors or patient factors. This study was aimed at comparing effectiveness of interrupted-X technique versus conventional continuous closure of rectus sheath in midline laparotomy in emergency setting. Methods: This study was conducted in a total of 100 patients underwent midline laparotomy for perforation peritonitis in emergency setting. Out of which 50 patients underwent rectus sheath closure by interrupted-X technique (group A) and 50 patients by conventional continuous closure (group B) using non-absorbable, monofilament, no.1 polypropylene suture. Necessary preoperative patient data, wound length, the time taken for rectus closure, length of the suture material used, post-operative complications like wound dehiscence, surgical site infection, period of hospital stay were recorded for analysis. Results: Preoperative patient data among both the groups were comparable. Group A was found to have less wound dehiscence (p=0.001 for partial and p=0.008 for complete) and less period of hospital stay (p=0.054), which were statistically significant. Surgical site infections were similar in both groups. Group B was found to have less time taken for closure (p=0.003) and less length of suture material used (p=0.003), which were statistically significant. Conclusions: Interrupted-X technique of rectus sheath closure reduces the rate of wound dehiscence and period of hospital stay, although it consumes more length of suture material and more time for suturing as compared to conventional continuous closure.